Development of Color Coding Media for the Development of Early Childhood English - Maghfiroh, Nur Lailatul; Zahro, Ianatuz; Siswono, Hendrik (Education and Development Research, 2025)
This study aims to develop Color Coding media as an instructional tool to enhance the English language skills of children aged 5–6 years at a selected early childhood education center. The research employed a Research and Development (R&D) methodology using the ADDIE model, which includes five systematic stages: analysis, design, development, implementation, and evaluation. The participants were kindergarten-aged children, and data were gathered using validation instruments completed by subject-matter experts in content, media, and design, alongside student-based evaluation tools. The validation process yielded results indicating a